The Dengue Vaccine Dilemma: Balancing the Individual and Population Risks and Benefits. - Jacqueline Deen (PLoS Medicine, 2016)
In a Perspective, Jacqueline Deeen discusses challenges in balancing the individual and population risks and benefits for CYD-TDV (Dengvaxia), the first available dengue vaccine.